Discovering your body system - Zubir, Nazira; Ahmad, Nora; Hamzah, Haliza; Teruk, Kamaril Azlah; Abdullah Sani, Siti Hajar; Mohd Sani, Rositi Mashani; Zahari, Shafiyyah Solehah; Mohd Nasohah, Nor Sa'adah (Pearson Malaysia Sdn. Bhd., 2012)
Discovering Your Body System is targeted to a wide range of readers,from the general public to university students. The presentation of the entire content is injected with some fun elements such as colourful figures, diagrams, illustrations, cartoon sketches, fun activities/experiments, photos, tables and misconceptions. These elements are to enhance the effectiveness of the text materials and facilitate the learning process. Readers can try out the simple yet fun activities/experiments with their family and friends to explore the biology concepts. The writing style is informal and relaxed and the contents are presented with a clear and simple sentences. New terms are carefully defined in a simple explanation. The concept and idea of the book is intended to make the reading materials more appealing and enjoyable to the readers. The materials covered in this book are fundamental topics in Human Physiology or Biology. The main objective of this book is to provide the readers with a logical, succinct and interesting presentation of physiology/biology concepts through exciting and different approaches. Readers are provided with interesting information and facts related to the human body system. The readers are encouraged by the authors to explore their body systems and try grasping the biology concepts in a fun way. This book can also act as an important guide and source for different level of students; SPM, STPM, Matriculation, A-level or university students. Students may find this book useful in their process of learning Biology. This may help them to strengthen their understanding and comprehension of some topics in Biology.